Digital Sakinah: Islamic Family Law Negotiation and the Resilience of Long-Distance Marriage (LDM) Couples - Ayulia Oktaviani Sutarman Putri (International Journal of Science and Society, 2026)
The phenomenon of Long-Distance Marriage (LDM) among civil servant couples introduces significant challenges to fulfilling key principles of Islamic Family Law, which traditionally emphasize physical presence, including financial support (nafkah), leadership (qawwam), and shared residence (maskan). This study addresses two central questions: how LDM couples adapt and negotiate their religious obligations, and how these processes lead to a reconceptualized form of sakinah in a modern context. Employing a qualitative approach, this research uses in-depth interviews with three LDM couples in Mempawah and analyzes the data through an interactive model. The findings reveal two adaptive patterns Delegation of Authority (Pattern A) and High Accountability (Pattern B) that transform the meaning of nafkah, qawwam, and maskan into digital practices. These adaptations culminate in the emergence of Digital Sakinah, a form of family harmony sustained through virtual communication, financial transparency, and emotional regulation, representing a contemporary expression of living law within Muslim families.Long Distance Marriage; Hukum Keluarga Islam; Qawwam Digital; Nafkah Digital; Sakinah Digital.